KEBIJAKAN HUTANG, KEBIJAKAN DIVIDEN, STRUKTUR KEPEMILIKAN DAN NILAI PERUSAHAAN - Najakh, Dzurroh Rif’atun; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of this research is to examine the influence of debt policy, dividend policy, and ownership structure to the firm value. Debt policy is measured by using debt to equity ratio (DER), dividend policy is measured by using dividend payout ratio (DPR), ownership structure is measured by using managerial ownership (KM), and institutional ownership (KI) and firm value is measured by using priceto book formula (PBV).This research has been done by using quantitative approach and multiple linear regression analysis method. The data is the secondary data which its origin is from property, real estate, and building construction companies which are listed in Indonesia Stock Exchange in 2011-2015 periods. The data collection technique has been carried out by using documentation and library study method. The sample collection has been done by using purposive sampling. The result of the research shows that debt policy does not give any influence to the firm value, dividend policy give positive influence to the firm value, and ownership structure which is proxy by maagerial ownership and instituional ownership does give any influence to the firm value.Keywords: debt policy, dividend policy, ownership structure, firm value